2008
DOI: 10.12693/aphyspola.113.1095
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Investigation of Heterostructures Based on Multiferroic BiFeO3

Abstract: We report heteroepitaxial growth of multiferroic BiFeO 3 thin films by RF magnetron sputtering on lattice-matched SrTiO3 substrates, as well as preparation and electrical properties of the heterostructures formed by growing BiFeO 3 thin films on highly conductive LaNiO 3 films and n-Si substrates. Nonlinear and rectifying current-voltage (I−U ) characteristics were revealed for the heterojunctions in a wide temperature range (T = 78-300 K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The theoretical predictions discussed above for the conductivity of BiFeO 3 are supported by recent experimental results. In addition to some sporadic studies on BiFeO 3 that suggest p ‐type conductivity, it was shown more directly that the conductivity of Ca‐doped BiFeO 3 could be reduced by several orders of magnitude if the ceramics were sintered in an oxygen‐poor atmosphere (e.g., in N 2 ), consistent with the p ‐type conduction behavior . Thus, Ca‐doped BiFeO 3 is a p ‐type semiconductor with an activation energy ( E a ) of ~0.27–0.4 eV when sintered in oxygen or air, whereas it is an ionic conductor with E a ~0.82–1.04 eV when sintered and cooled in nitrogen (Fig.…”
Section: Dielectric Permittivity Electrical Conductivity and Defectsmentioning
confidence: 82%
“…The theoretical predictions discussed above for the conductivity of BiFeO 3 are supported by recent experimental results. In addition to some sporadic studies on BiFeO 3 that suggest p ‐type conductivity, it was shown more directly that the conductivity of Ca‐doped BiFeO 3 could be reduced by several orders of magnitude if the ceramics were sintered in an oxygen‐poor atmosphere (e.g., in N 2 ), consistent with the p ‐type conduction behavior . Thus, Ca‐doped BiFeO 3 is a p ‐type semiconductor with an activation energy ( E a ) of ~0.27–0.4 eV when sintered in oxygen or air, whereas it is an ionic conductor with E a ~0.82–1.04 eV when sintered and cooled in nitrogen (Fig.…”
Section: Dielectric Permittivity Electrical Conductivity and Defectsmentioning
confidence: 82%
“…The cation vacancies form shallow acceptor defects. Vengalis et al found that BiFeO 3 thin films prepared by RF magnetron sputtering displayed p-type semiconducting behavior [ 37 ]. Masó and West found that Ca-doped BiFeO 3 samples that had been heat-treated in O 2 at ~125 bar were p-type semiconducting [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The estimated work function is 4.2 eV and its Fermi level is about 0.2 eV, which lies below the bottom of conduction band [7]. BiFeO 3 is a p-type semiconductor [33][34][35][36], whose band gap varies from 2.0 to 2.7 eV and its Fermi level lies close to its valance band. Here the band gap of BFO is calculated to be 2.07 eV according to the UV-vis DRS spectra.…”
Section: Discussion On Mechanismmentioning
confidence: 97%